Binder, wide-temperature-range high-temperature lubricating paint, preparation method of wide-temperature-range high-temperature lubricating paint, coating and coating method

By preparing the combination of modified binder and nanocomposite, the problem of high wear rate of power equipment coatings under high temperature conditions is solved, and a coating with low friction coefficient, low wear rate, good corrosion resistance and high temperature lubrication performance is achieved in a wide temperature range.

CN119735970AActive Publication Date: 2025-04-01LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411741799.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-01
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing power equipment coatings have high wear rate under high temperature conditions, making it difficult to adapt to the problem of wide temperature range.

Method used

A method of preparing a binder is adopted, including adding chromium trioxide and aluminum hydroxide to the aqueous phosphoric acid solution, followed by adding gas-phase silica and boron oxide, and obtaining a modified binder after insulation reaction and natural cooling. The binder is ground and dispersed with aminated boron nitride, low-melting glass powder, aluminum pigment and anti-wear pigment filler to form a nanocomposite, which is evenly distributed in the mesh structure of the binder to form a high-temperature lubricating coating.

Benefits of technology

It realizes a coating with low friction coefficient, low wear rate, good corrosion resistance and high temperature lubrication performance in a wide temperature range (room temperature ~ 800℃), which significantly improves the working efficiency and reliability of the power equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735970A_ABST
    Figure CN119735970A_ABST
Patent Text Reader

Abstract

The invention provides a binder, a wide-temperature-range high-temperature lubricating coating, a preparation method of the wide-temperature-range high-temperature lubricating coating, a coating and a coating method, and the preparation method of the wide-temperature-range high-temperature lubricating coating comprises the following steps: adding aminated boron nitride, low-melting-point glass powder, an aluminum pigment and an anti-wear pigment filler into a crushing device in proportion, adding water, and crushing and grinding for 12-48 hours to obtain slurry; adding a water-phase dispersion liquid of a binder into the slurry, then adding water, stirring and mixing, and premixing the coating; and stirring and dispersing the premixed coating to obtain the finished product wide-temperature-range high-temperature lubricating coating. According to the coating disclosed by the invention, boron oxide and fumed silica modified inorganic phosphate resin is used as a binder, amination modified hexagonal boron nitride is used as a main lubricating anti-corrosion filler, and low-melting-point glass powder and aluminum pigment are used as anti-corrosion toughening agents, and are matched with other functional fillers and auxiliaries; the coating obtained through high-temperature curing can be used in a wide temperature range and has a lower wear rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coating anti-corrosion, and in particular to an adhesive, a wide temperature range high temperature lubricating coating and a preparation method thereof, a coating and a coating method. Background Art

[0002] Due to the high humidity and high salt environment of the marine atmosphere, aircraft engine and gas turbine components, such as fasteners, bearings and other moving parts, work in a strongly coupled wear-corrosion condition, which can easily lead to accelerated damage to the metal matrix. Once they fail, they will affect the working efficiency and reliability of the power equipment at the very least, and may even lead to safety accidents. Therefore, lubrication and anti-corrosion treatment of their surfaces is crucial.

[0003] However, the operating temperature of the fasteners and moving parts of the bearings of power equipment is as high as 600-800℃. At this temperature stage, lubricating grease and conventional organic solid lubricating adhesive coatings have long been ineffective. In addition, there are large temperature fluctuations in the working process of power equipment, and protective coatings must develop towards a wide temperature range, higher temperature, and lower global friction coefficient and wear rate. However, the current domestic high-temperature lubricating coatings are not universal. The friction coefficient is low only in some temperature ranges. In other temperature ranges, the friction coefficient is greater than 0.2 and the wear rate is high. The anti-corrosion performance of the coating is also poor. Compared with similar foreign products, there is still a large gap. It is of great significance to develop a wide temperature range, high temperature resistant lubricating and anti-corrosion coating. Summary of the invention

[0004] The present application provides an adhesive, a wide temperature range high temperature lubricating coating and its preparation method, a coating and a coating method, which are used to solve the problem that the above-mentioned existing power equipment coatings have a high wear rate under high temperature conditions and are difficult to adapt to a wide temperature range.

[0005] In a first aspect, the present application provides a method for preparing a binder, comprising the following steps:

[0006] Add chromium trioxide to the phosphoric acid aqueous solution, stir and dissolve, heat to 80-85° C., add aluminum hydroxide to the solution, heat to 100-140° C. after it is completely dissolved, and keep the temperature for 1-3 hours to obtain a chromium aluminum phosphate binder;

[0007] Add fumed silica and boron oxide to the chromium aluminum phosphate binder, keep the temperature to react for 1 to 3 hours, and then naturally cool to room temperature to obtain a modified binder.

[0008] The method for preparing a wide temperature range high-temperature lubricating coating of the present application is carried out at room temperature, so it has the characteristics of mild reaction conditions and easy control.

[0009] In the method of the present application, the amino boron nitride, low melting point glass powder, aluminum pigment and anti-wear pigment filler are ground and dispersed. The binder has a cross-linked network structure at the microscopic level, so the addition of the binder provides a good accommodation space for these nanocomposites. After stirring and dispersing, the nanocomposites formed by the above materials are evenly distributed in the network structure provided by the binder, and after curing, a uniform and dense protective coating can be formed on the surface of the substrate, thereby exerting the anti-wear and lubricating characteristics of each component.

[0010] In a second aspect, the present application provides an adhesive, including an adhesive prepared by the method for preparing the adhesive described in any one of the first aspects above.

[0011] In a third aspect, the present application provides a method for preparing a wide temperature range high temperature lubricating coating, comprising the following steps:

[0012] Add amino boron nitride, low melting point glass powder, aluminum pigment and anti-wear pigment filler into a crushing device according to proportion, add water, crush and grind for 12 to 48 hours to obtain slurry;

[0013] Adding the aqueous dispersion of the binder provided in the second aspect to the slurry, and then adding water, stirring and mixing, to premix the coating;

[0014] The premixed coating is stirred and dispersed to obtain a finished product of a wide temperature range high temperature lubricating coating.

[0015] Optionally, the amination boron nitride is prepared as follows:

[0016] Adding boron nitride powder, urea and deionized water into a ball mill, and grinding at a speed of 400 to 600 rpm for 24 to 72 hours to obtain a crushed slurry;

[0017] The crushed pulp is filtered, and the filter cake is washed with deionized water until the filtrate is neutral, and then dried to obtain the amination boron nitride powder;

[0018] The mass ratio of boron nitride, urea and water is 1-5:30-60:20-40.

[0019] Optionally, the amount of aqueous dispersion of binder added is 25 to 35 parts by weight, the amount of amino boron nitride added is 5 to 15 parts, the amount of low-melting point glass powder added is 3 to 5 parts by weight, the amount of aluminum pigment added is 3 to 5 parts by weight, the amount of anti-wear color filler added is 10 to 20 parts, and the amount of water added is 20 to 60 parts.

[0020] Optionally, the solid content of the aqueous dispersion of the binder is 60-65 wt %;

[0021] During the stirring and dispersing process, the stirring rate is 2000-5000 rpm and the dispersing time is 10-20 min.

[0022] In a fourth aspect, the present application provides a wide temperature range high temperature lubricating coating, including a coating prepared by the preparation method of the wide temperature range high temperature lubricating coating described in any one of the third aspects above.

[0023] The wide temperature range high temperature lubricating coating of the present application has the following advantages:

[0024] 1) The micro-inorganic substances in the coating components will not be released by organic gas during use, thus avoiding the escape of volatile organic matter and causing pollution to the environment.

[0025] 2) Boron hexanitride in the coating has the characteristics of two-dimensional lamellar structure, large specific surface area, stable chemical properties, etc. It is dispersed in the coating and can effectively shield the corrosive medium, making the coating have excellent corrosion resistance.

[0026] 3) Low-melting-point glass powder and aluminum pigment are used as anti-corrosion toughening agents. The low-melting-point glass powder melted at high temperature penetrates and seals the fine pores of the coating, enhancing the anti-corrosion and antioxidant capabilities of the coating. At the same time, a glaze lubricating layer is formed on the surface of the coating through the "sweating" effect, thereby improving the high-temperature lubrication capability of the coating. The aluminum pigment can provide cathodic protection for the substrate, further improving the corrosion resistance of the coating.

[0027] In a fifth aspect, the present application provides a coating method, comprising the following steps:

[0028] The wide temperature range high temperature lubricating coating provided in the fourth aspect is evenly applied to the surface of the substrate and allowed to dry for 1 to 18 hours to form a pre-coating layer on the surface of the substrate;

[0029] Placing the substrate with the pre-coated coating on the surface in a heating device, heating and curing in an air atmosphere to form a coating on the surface of the substrate;

[0030] During the heating and curing process, the temperature is first raised from room temperature to 120-150°C at a heating rate of 2-3°C / min, and the temperature is kept at this temperature for curing for 1-1.5 hours; then the temperature is raised to 305-315°C at a heating rate of 1-2°C / min, and the temperature is kept at this temperature for curing for 1-1.5 hours, and then the temperature is naturally cooled;

[0031] The thickness of the cured coating is 15 to 30 μm.

[0032] The coating method of the present application, combined with the use of the above-mentioned wide temperature range high-temperature lubricating coating, can provide a high-strength coating with strong adhesion, impact resistance, heat resistance, thermal shock resistance, wide temperature adaptation range, corrosion resistance, wear resistance, and high-temperature lubrication.

[0033] In a sixth aspect, the present application provides a coating, which is prepared by the coating method provided in the fifth aspect, and the thickness of the coating is 15 to 30 μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0035] Figure 1 This is a test result diagram of the coating adhesion of the coatings of Example 1 and Example 2 of the present application after the oxidation test;

[0036] Figure 2 This is a comparison diagram of the outer tubes of the coatings of Example 1 and Example 2 of the present application before and after the thermal shock test;

[0037] Figure 3 The friction coefficient curves of the coatings of Example 1 and Example 2 of the present application before and after high-temperature oxidation at 800° C. for 12 hours;

[0038] Figure 4 The XRD patterns of unmodified aluminum chromium phosphate binder at different temperatures;

[0039] Figure 5 XRD patterns of modified aluminum chromium phosphate binder at different temperatures. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.

[0041] In a first aspect, the present application provides a method for preparing a binder, comprising the following steps:

[0042] Add chromium trioxide to the phosphoric acid aqueous solution, stir to dissolve, and heat to 80-85° C. to obtain an acidic solution;

[0043] Add aluminum hydroxide to the acidic solution, raise the temperature to 100-140° C. after it is completely dissolved, and keep the temperature to react for 1-3 hours to obtain a precursor solution;

[0044] Add fumed silica and boron oxide to the precursor solution, keep the temperature to react for 1 to 3 hours, and then naturally cool to room temperature to obtain a binder.

[0045] In the present application, the precursor solution is the unmodified aluminum chromium phosphate binder, and the "binder" referred to in the present application is the modified aluminum chromium phosphate binder.

[0046] In the present application, the binder uses acid chromium aluminum phosphate, and the above-mentioned phosphate is modified with boron oxide and fumed silica: the addition of boron oxide can introduce reversible BOP and BOB covalent bonds in the POP network, increase the amorphous phase content of the resin, enhance the toughness of the phosphate resin, and reduce the thermal stress caused by phase change; the low-melting-point boron oxide also gives the resin the ability to repair tiny thermal stress cracks during thermal cycling, greatly improving the high temperature resistance and thermal shock resistance of the coating.

[0047] The large specific surface area and abundant surface silanol groups of fumed silica make it very easy to adsorb on the surface of the lubricant, preventing oxygen atoms from contacting it, thereby improving the lubricant's high-temperature antioxidant properties. At the same time, it improves the lubricant's dispersibility and interfacial bonding in the resin, reduces the porosity of the coating, and increases the density of the coating. The fumed silica nanoparticles attached to the surface of the lubricant act as "micro-bearings", reducing the friction coefficient while repairing the friction surface, greatly improving the coating's anti-friction and anti-wear properties.

[0048] The preparation method of the binder of the present application uses acid chromium aluminum phosphate as the main material and is supplemented with fumed silica and boron oxide. The above materials react at 100-140°C to introduce reversible BOP and BOB covalent bonds into the POP network of acid chromium aluminum phosphate, thereby increasing the amorphous phase content of the resin, enhancing the toughness of the phosphate resin, and simultaneously giving the coating high temperature resistance and thermal shock resistance. The addition of fumed silica can improve the friction reduction and anti-wear performance of the coating. The method for preparing the binder of the present application has short steps, is easy to operate, and has the characteristics of being easy to implement and saving time.

[0049] In a second aspect, the present application provides an adhesive, including an adhesive prepared by the method for preparing the adhesive described in any one of the first aspects above.

[0050] The beneficial effects of the adhesive provided in the present application are as described in the preparation method of the adhesive described in the first aspect and will not be repeated here.

[0051] In a third aspect, the present application provides a method for preparing a wide temperature range high temperature lubricating coating, comprising the following steps:

[0052] Add amino boron nitride, low melting point glass powder, aluminum pigment and anti-wear pigment filler into a crushing device according to proportion, add water, crush and grind for 12 to 48 hours to obtain slurry;

[0053] Adding the aqueous dispersion of the binder provided in the second aspect to the slurry, and then adding water, stirring and mixing, to premix the coating;

[0054] The premixed coating is stirred and dispersed to obtain a finished product of a wide temperature range high temperature lubricating coating.

[0055] In the present application, the aqueous dispersion of the binder is a suspension formed by mixing the binder with water.

[0056] The crushing device of the present application is a ball milling device, and the rotation speed is adjusted to 400-600 rpm during ball milling.

[0057] Amination boron nitride, white powder, particle size 3 ~ 5μm; low melting point glass powder, white powder, particle size ≤10μm; aluminum pigment, silver gray powder, particle size ≤10μm; anti-wear pigment filler is one or more of aluminum oxide, silicon oxide, chrome green, titanium dioxide, cobalt black, copper chrome black, etc., with particle size ≤10μm.

[0058] Hexagonal boron nitride is used as the main lubricating and corrosion-inhibiting agent. Hexagonal boron nitride has a low friction coefficient and excellent high-temperature resistance. It is a good high-temperature lubricating filler. In addition, hexaboron nitride has the characteristics of two-dimensional lamellar structure, large specific surface area, and stable chemical properties. When dispersed in the coating, it can effectively shield the corrosive medium and improve the corrosion resistance of the coating.

[0059] Low-melting-point glass powder and aluminum pigment are used as anti-corrosion and toughening agents. The low-melting-point glass powder melted at high temperature penetrates and seals the fine pores of the coating, enhancing the anti-corrosion and antioxidant capabilities of the coating. At the same time, a glaze lubrication layer is formed on the coating surface through the "sweating" effect, thereby improving the high-temperature lubrication capability of the coating. Aluminum pigment (including aluminum powder) can provide cathodic protection for the substrate, further improving the corrosion resistance of the coating.

[0060] Through the synergistic combination of adhesives, lubricating preservatives, and anti-corrosion toughening agents, the coating can be used in a wide temperature range from room temperature to 800°C, with a friction coefficient of less than 0.2 and a wear rate of less than 10. -5 m 3 / Nm, and the salt spray resistance of the coating is greater than 500h.

[0061] The method for preparing a wide temperature range high-temperature lubricating coating of the present application is carried out at room temperature, so it has the characteristics of mild reaction conditions and easy control.

[0062] In the method of the present application, the amino boron nitride, low melting point glass powder, aluminum pigment and anti-wear pigment filler are ground and crushed. Long-term ball milling not only improves the compatibility between the various materials, but also, at the microscopic level, the long-term grinding and crushing makes the grains of the various materials finer, and it is easier for them to form nanocomposites through intermolecular forces. The binder has a cross-linked network structure at the microscopic level, so the addition of the binder provides a good accommodation space for these nanocomposites. After stirring and dispersing, the nanocomposites formed by the above materials are evenly distributed in the network structure provided by the binder, and after curing, they can form a uniform and dense protective coating on the surface of the substrate, thereby giving full play to the characteristics of each component.

[0063] Optionally, the amination boron nitride is prepared as follows:

[0064] Adding boron nitride powder, urea and deionized water into a ball mill, and grinding at a speed of 400 to 600 rpm for 24 to 72 hours to obtain a crushed slurry;

[0065] The crushed pulp is filtered, and the filter cake is washed with deionized water until the filtrate is neutral, and then dried to obtain the amination boron nitride powder;

[0066] The mass ratio of boron nitride, urea and water is 1-5:30-60:20-40.

[0067] In the present application, the amination of boron nitride is achieved by using urea as an ammonia source and through long-term ball milling. During the ball milling process, the ball milling will refine the grains of the boron nitride powder and distort the lattice, which is conducive to the formation of a boron nitride-urea nanoscale composite structure. Moreover, under the conditions of high-speed ball milling, urea decomposes and deaminates to dissociate the N-containing group (-NH2), thereby achieving the amination of boron nitride.

[0068] Optionally, the amount of aqueous dispersion of binder added is 25 to 35 parts by weight, the amount of amino boron nitride added is 5 to 15 parts, the amount of low-melting point glass powder added is 3 to 5 parts by weight, the amount of aluminum pigment added is 3 to 5 parts by weight, the amount of anti-wear color filler added is 10 to 20 parts, and the amount of water added is 20 to 60 parts.

[0069] Optionally, the solid content of the aqueous dispersion of the binder is 60-65 wt %;

[0070] During the stirring and dispersing process, the stirring rate is 2000-5000 rpm and the dispersing time is 10-20 min.

[0071] In the present application, stirring and dispersing is the process of mixing and blending the various substances in the premixed coating. In the present application, a high-speed disperser is used for dispersion, because only under the above-mentioned rotation speed conditions of 2000 to 5000 rpm can the strong shear force make the various components in the premixed coating more evenly mixed and improve the compatibility of the components.

[0072] In a fourth aspect, the present application provides a wide temperature range high temperature lubricating coating, including a coating prepared by the preparation method of the wide temperature range high temperature lubricating coating described in any one of the third aspects above.

[0073] The wide temperature range high temperature lubricating coating of the present application has the following advantages:

[0074] 1) The micro-inorganic substances in the coating components will not be released by organic gas during use, thus avoiding the escape of volatile organic matter and causing pollution to the environment.

[0075] 2) Boron hexanitride in the coating has the characteristics of two-dimensional lamellar structure, large specific surface area, stable chemical properties, etc. It is dispersed in the coating and can effectively shield the corrosive medium, making the coating have excellent corrosion resistance.

[0076] 3) Low-melting-point glass powder and aluminum pigment are used as anti-corrosion toughening agents. The low-melting-point glass powder melted at high temperature penetrates and seals the fine pores of the coating, enhancing the anti-corrosion and antioxidant capabilities of the coating. At the same time, a glaze lubricating layer is formed on the surface of the coating through the "sweating" effect, thereby improving the high-temperature lubrication capability of the coating. The aluminum pigment can provide cathodic protection for the substrate, further improving the corrosion resistance of the coating.

[0077] In a fifth aspect, the present application provides a coating method, comprising the following steps:

[0078] The wide temperature range high temperature lubricating coating provided in the fourth aspect is evenly applied to the surface of the substrate and allowed to dry for 1 to 18 hours to form a pre-coating layer on the surface of the substrate;

[0079] Placing the substrate with the pre-coated coating on the surface in a heating device, heating and curing in an air atmosphere to form a coating on the surface of the substrate;

[0080] During the heating and curing process, the temperature is first raised from room temperature to 120-150°C at a heating rate of 2-3°C / min, and the temperature is kept at this temperature for curing for 1-1.5 hours; then the temperature is raised to 305-315°C at a heating rate of 1-2°C / min, and the temperature is kept at this temperature for curing for 1-1.5 hours, and then the temperature is naturally cooled;

[0081] The thickness of the cured coating is 15 to 30 μm.

[0082] In the coating method of the present application, air-drying the coating can reduce the occurrence of adverse consequences such as cracking and breakage of the coating during the subsequent heating and curing process.

[0083] In this application, the process of heating and curing is not only the process of drying and removing water molecules in the coating, but also the process of reaction of various components in the coating. The binder in the coating is not only the carrier of the other components, but also the key adhesive. During the heating and curing process, the water in the coating applied to the surface of the substrate is gradually evaporated under the heat preservation curing conditions of 120-150°C, leaving the materials other than water in the coating. As the curing temperature gradually increases to 305-315°C, during the curing process at this temperature, a network structure of the binder is formed, and at the same time, reversible BOP and BOB covalent bonds are introduced into the POP network, which increases the amorphous phase content of the resin and enhances the toughness of the phosphate resin, thereby providing a high-strength coating that is impact-resistant, heat-resistant, heat-shock-resistant, has a wide temperature range, is corrosion-resistant, wear-resistant, and self-lubricating.

[0084] Moreover, during the high-temperature curing process, the molecular movement on the surface of the substrate will also be accelerated, so that some molecules or atoms on the surface of the substrate can be embedded in the coating. Similarly, the atoms or molecules in the coating can also enter the molecular or atomic layer on the surface of the substrate, thereby making the substrate and the coating more closely bonded and further improving the adhesion of the coating.

[0085] In addition, since the aluminum pigment in the paint is a paint with aluminum powder as the main component, the aluminum powder undergoes oxidation reaction to become aluminum oxide during the high-temperature curing process in the air atmosphere, which can form a dense protective film, thereby improving the anti-corrosion performance of the coating.

[0086] Therefore, the coating method of the present application, combined with the use of the above-mentioned wide temperature range high-temperature lubricating coating, can provide a high-strength coating with strong adhesion, impact resistance, heat resistance, thermal shock resistance, wide temperature adaptation range, corrosion resistance, wear resistance, and high-temperature lubrication.

[0087] In a sixth aspect, the present application provides a coating, which is prepared by the coating method provided in the fifth aspect, and the thickness of the coating is 15 to 30 μm.

[0088] The main performance indicators of the wide temperature range high temperature resistant solid lubricating coating of this application are as follows:

[0089] (1) Coating appearance: black-gray (cobalt black is used as anti-wear pigment filler, and the specific color is related to the color of the anti-wear pigment filler), uniform, and without obvious defects.

[0090] (2) Coating adhesion: Grade 1 (GB / T 9286).

[0091] (3) Coating flexibility: 1-2 mm, GB / T 1731.

[0092] (4) Impact resistance of coating: 50cm, GB / T 1732.

[0093] (5) Heat resistance of coating: 800±10℃, constant temperature for 12h, the coating is intact without cracks, softening, falling off, bubbles, etc., and the coating adhesion is level 1.

[0094] (6) Thermal shock resistance of coating: Thermal shock test at room temperature to 800℃, 50 times, the coating is intact, without cracks, no falling off, etc.

[0095] (7) In the wide temperature range of 20℃~800℃, the friction coefficient is 0.1~0.2. The test conditions are: ball-on-disc contact, reciprocating wear, load 10N, frequency 2Hz, amplitude 6mm, and the dual is a 6mm ZrO2 ball.

[0096] (8) In the wide temperature range of 20~800℃, the wear rate is less than 10-5m3 / Nm, and the test conditions are the same as above.

[0097] (9) Neutral salt spray test, 500h, no corrosion on the coating surface.

[0098] The beneficial effects of the coating of the present application are as described in the coating method of the fifth aspect above and will not be repeated here.

[0099] Example

[0100] Example 1

[0101] A wide temperature range high temperature lubricating coating is prepared according to the following method:

[0102] S101. Add 6 parts of amino boron nitride, 3 parts of low-melting-point glass powder, 3 parts of aluminum pigment, 10 parts of anti-wear pigment (cobalt black) and 25 parts of water into a ball mill by weight, and grind them at a speed of 400 rpm for 48 hours to obtain a slurry.

[0103] S102, adding 25 parts by weight of an aqueous dispersion of a binder (solid content of 65%) to the slurry, and then adding 25 parts by weight of water, stirring and mixing evenly to obtain a premixed coating.

[0104] S103, adding the premixed coating into a high-speed disperser, stirring and dispersing at a stirring rate of 4500 rpm for 10 minutes, to obtain a finished product of a wide temperature range high-temperature lubricating coating.

[0105] Example 2

[0106] A wide temperature range high temperature lubricating coating is prepared according to the following method:

[0107] S201. Add 8 parts of amino boron nitride, 3 parts of low-melting-point glass powder, 3 parts of aluminum pigment, 8 parts of anti-wear pigment (cobalt black) and 25 parts of water into a ball mill by weight, and grind them at a speed of 600 rpm for 48 hours to obtain a slurry.

[0108] S202, add 25 parts by weight of an aqueous dispersion of a binder (solid content of 65%) to the slurry, and then add 25 parts by weight of water, stir and mix evenly to obtain a premixed coating.

[0109] S203, adding the premixed coating into a high-speed disperser, stirring and dispersing at a stirring rate of 4500 rpm for 10 minutes, to obtain a finished product of a wide temperature range high-temperature lubricating coating.

[0110] Example 3

[0111] A wide temperature range high temperature lubricating coating is prepared according to the following method:

[0112] S301. Add 15 parts of amino boron nitride, 5 parts of low-melting-point glass powder, 5 parts of aluminum pigment, 20 parts of anti-wear pigment (cobalt black) and 30 parts of water into a ball mill by weight, and grind them at a speed of 400 rpm for 12 hours to obtain a slurry.

[0113] S302, add 25 parts by weight of an aqueous dispersion of a binder (solid content of 65%) to the slurry, and then add 30 parts by weight of water, stir and mix evenly to obtain a premixed coating.

[0114] S303, adding the premixed coating into a high-speed disperser, stirring and dispersing at a stirring rate of 5000 rpm for 10 to 20 minutes, to obtain a finished product of a wide temperature range high-temperature lubricating coating.

[0115] Example 4

[0116] A wide temperature range high temperature lubricating coating is prepared according to the following method:

[0117] S401. Add 5 parts of amino boron nitride, 4 parts of low-melting-point glass powder, 4 parts of aluminum pigment, 15 parts of anti-wear pigment (cobalt black) and 10 parts of water into a ball mill by weight, and grind them at a speed of 500 rpm for 36 hours to obtain a slurry.

[0118] S402, add 35 parts by weight of an aqueous dispersion of a binder (solid content of 65%) to the slurry, and then add 10 parts by weight of water, stir and mix evenly to obtain a premixed coating.

[0119] S403, adding the premixed coating into a high-speed disperser, stirring and dispersing at a stirring rate of 2000 rpm for 20 minutes, to obtain a finished product of a wide temperature range high-temperature lubricating coating.

[0120] Comparative Example 1

[0121] The remaining operations are the same as those in Example 1, except that fumed silica and boron oxide are not added to the binder.

[0122] 1. Preparation of amino boron nitride

[0123] The amino boron nitride in the above examples and comparative examples was prepared as follows:

[0124] Add boron nitride powder, urea and deionized water into a ball mill, and grind them at a speed of 500 rpm for 72 hours to obtain a crushed slurry;

[0125] The crushed pulp is filtered, and the filter cake is washed with deionized water until the filtrate is neutral, and then dried to obtain the amination boron nitride powder;

[0126] The mass ratio of boron nitride, urea and water is 1:30:30.

[0127] 2. Preparation of binder

[0128] 1) The binders used in the above-mentioned Examples 1, 3 and 4 were prepared as follows:

[0129] Z101, add chromium trioxide to a 60wt% phosphoric acid aqueous solution, stir to dissolve, and heat to 85°C to obtain an acidic solution;

[0130] Z102, adding aluminum hydroxide to the acidic solution, raising the temperature to 120°C after it is completely dissolved, and keeping the temperature to react for 2 hours to obtain a precursor glue solution;

[0131] Z103. Add fumed silica and boron oxide to the precursor glue solution, keep the reaction warm for 2 hours, and then naturally cool to room temperature to obtain a binder.

[0132] The molar ratio of aluminum hydroxide to phosphoric acid is 0.26:1;

[0133] The molar ratio of aluminum hydroxide to chromium oxide is 3.4:1;

[0134] The amount of fumed silica is 1.9% of the binder mass;

[0135] The amount of boron oxide used is 1.4% of the binder mass.

[0136] 2) The binder used in the above embodiment 2 is prepared according to the following method:

[0137] Z201, add chromium trioxide to a 60wt% phosphoric acid aqueous solution, stir to dissolve, and heat to 85°C to obtain an acidic solution;

[0138] Z202, add aluminum hydroxide to the acidic solution, raise the temperature to 120°C after it is completely dissolved, and keep the temperature for 2 hours to obtain a precursor solution;

[0139] Z203. Add fumed silica and boron oxide to the precursor solution, keep the reaction warm for 2 hours, and then naturally cool to room temperature to obtain a binder.

[0140] The molar ratio of aluminum hydroxide to phosphoric acid is 0.35:1;

[0141] The molar ratio of aluminum hydroxide to chromium oxide is 3:1;

[0142] The amount of fumed silica is 2.4% of the binder mass;

[0143] The amount of boron oxide used is 1.6% of the binder mass.

[0144] The aqueous dispersion of the binder is a dispersion having a corresponding solid content obtained by adding deionized water to the binder and mixing.

[0145] 3. Coating preparation

[0146] The coatings prepared by the methods of Examples 1 to 4 and Comparative Example 1 are made into corresponding coatings according to the following method.

[0147] The wide temperature range high temperature lubricating coating is evenly applied to the treated substrate surface by spraying, and left to dry for 8 hours to form a pre-coating on the substrate surface.

[0148] The substrate with the pre-coating layer attached to the surface is placed in a heating device and heated in an air atmosphere. The heating process is first heated from room temperature to 150°C at a heating rate of 3°C / min, and kept warm for curing for 1.5 hours; then heated to 305°C at a heating rate of 2°C / min, kept warm for curing for 1.5 hours, and then naturally cooled to form a coating on the surface of the substrate; the thickness of the coating after curing is controlled to be 20μm±0.5μm.

[0149] Experimental example

[0150] The coatings prepared by the methods of Examples 1 to 4 and Comparative Example 1 were subjected to the following experiments:

[0151] Experimental Example 1

[0152] After the coated substrate was oxidized at 900℃ for 48h, the coating adhesion was tested using GB / T 5210-2006 "Paint and varnish pull-off adhesion test"; the coated substrate was subjected to a neutral salt spray resistance test according to the method of GB / T 10125-2021 "Artificial atmosphere corrosion test-salt spray test" (the sample was not cross-cut, and the test endpoint was the appearance of rust spots on the sample). The results are shown in Table 1:

[0153] Coating Adhesion(MPa) Salt spray resistance (h) Example 1 15.91 1555 Example 2 12.23 1472 Example 3 15.46 1485 Example 4 14.98 1508 Comparative Example 1 8.77 456

[0154] at the same time Figure 1 Example 1 ( Figure 1 (a)) and Example 2 ( Figure 1 The coating in (b) is tested for adhesion after thermal oxidation at 900℃ for 48h.

[0155] Experimental Example 2

[0156] The coatings of Example 1 and Example 2 were subjected to thermal shock tests (room temperature to 800°C thermal shock test, i.e., the coatings were heated to 800°C and then quickly cooled in cold water at room temperature) 50 times according to the method provided in GB / T 42259-2022 "Methods for testing the thermal cycle resistance and thermal shock performance of thermal barrier coatings of metals and other inorganic coatings" and the appearance of the coatings was observed. The results are as follows: Figure 2 As shown, Figure 2 (a) is the appearance of the coating of Example 1 before thermal shock. Figure 2(b) is the appearance of the coating of Example 1 after thermal shock. Figure 2 (c) is the appearance of the coating of Example 2 before thermal shock. Figure 2 (d) is the appearance of the coating of Example 2 after thermal shock. Figure 2 It can be seen from the pictures that after the coatings of Example 1 and Example 2 were subjected to the thermal shock test, the appearance of the coatings did not change significantly, which indicates that the coatings formed by the coatings prepared by the method of the present application have excellent thermal shock resistance, that is, the coatings made by the coatings of the present application can be used in a wide temperature range of room temperature to 800°C and exhibit superior performance.

[0157] Experimental Example 3

[0158] The coatings of Examples 1 and 2 were oxidized at 800°C for 12 hours and subjected to friction tests. The CSM friction machine was used, with 6mm alumina ceramic balls, a frequency of 2Hz, a friction time of 30min, a friction length of 5mm, a load of 5N, and a friction mode of reciprocating dry friction. The friction coefficient was measured, and the results were as follows: Figure 3 shown.

[0159] Figure 3 The abnormal value of the friction coefficient curve after high temperature oxidation in Example 1 at 1300s is caused by measurement error. Figure 3 The friction coefficient curve shows that after high-temperature oxidation, the friction coefficient of the coatings of Example 1 and Example 2 is still maintained in the low friction coefficient range of about 0.15 during the test time, which indicates that the coating prepared by the coating of the present application has excellent anti-friction performance, and also reflects its low wear rate and good lubricity under high temperature conditions.

[0160] Figure 4 and Figure 5 The XRD patterns of the unmodified aluminum chromium phosphate binder (i.e., the precursor solution) and the modified aluminum chromium phosphate binder (i.e., the binder prepared by the method of the present application) at different temperatures are shown, and it can be found that the unmodified binder is completely transformed into a crystalline phase after high-temperature heating, and a large stress is generated during the high-temperature phase change, resulting in poor heat resistance and thermal shock resistance of the coating. The modified resin still retains a large amount of amorphous phase at high temperature, which alleviates the thermal stress caused by the high-temperature phase change during the thermal cycle, and improves the heat resistance and thermal shock resistance of the coating.

[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a binder, characterized in that: The steps include: Add chromium trioxide to the phosphoric acid aqueous solution, stir to dissolve, and heat to 80-85° C. to obtain an acidic solution; Add aluminum hydroxide to the acidic solution, raise the temperature to 100-140° C. after it is completely dissolved, and keep the temperature to react for 1-3 hours to obtain a precursor solution; Add fumed silica and boron oxide to the precursor solution, keep the temperature to react for 1 to 3 hours, and then naturally cool to room temperature to obtain a binder.

2. The method for preparing the adhesive according to claim 1, characterized in that: The concentration of the phosphoric acid aqueous solution is 55-70wt%; The molar ratio of aluminum hydroxide to phosphoric acid is 0.25-0.4:1; The molar ratio of aluminum hydroxide to chromium oxide is 2 to 4:1; The amount of fumed silica is 1-5% of the binder mass; The amount of boron oxide used is 1 to 5% of the mass of the binder.

3. A binder, characterized in that: The invention comprises preparing the product by the method provided by claim 1 or 2.

4. A method for preparing a wide temperature range high temperature lubricating coating, characterized in that: The steps include: Add amino boron nitride, low melting point glass powder, aluminum pigment and anti-wear pigment filler into a crushing device according to proportion, add water, crush and grind for 12 to 48 hours to obtain slurry; Adding the aqueous dispersion of the binder provided in claim 3 to the slurry, and then adding water, stirring and mixing, to premix the coating; The premixed coating is stirred and dispersed to obtain a finished product of a wide temperature range high temperature lubricating coating.

5. The method for preparing a wide temperature range high temperature lubricating coating according to claim 4, characterized in that: The amination boron nitride is prepared according to the following method: Adding boron nitride powder, urea and deionized water into a ball mill, and grinding at a speed of 400 to 600 rpm for 24 to 72 hours to obtain a crushed slurry; The crushed pulp is filtered, and the filter cake is washed with deionized water until the filtrate is neutral, and then dried to obtain the amination boron nitride powder; The mass ratio of the boron nitride, urea and water is 1-5:30-60:20-40.

6. The method for preparing a wide temperature range high temperature lubricating coating according to claim 4, characterized in that: The amount of the aqueous dispersion of the binder added is 25 to 35 parts by weight, the amount of amino boron nitride added is 5 to 15 parts, the amount of low-melting point glass powder added is 3 to 5 parts by weight, the amount of aluminum pigment added is 3 to 5 parts by weight, the amount of anti-wear color filler added is 10 to 20 parts, and the amount of water added is 20 to 60 parts.

7. The method for preparing a wide temperature range high temperature lubricating coating according to claim 4, characterized in that: The solid content of the aqueous dispersion of the binder is 60-65wt%; During the stirring and dispersing process, the stirring rate is 2000-5000 rpm and the dispersing time is 10-20 min.

8. A wide temperature range high temperature lubricating coating, characterized in that: The method comprises preparing the product by the method described in any one of claims 4 to 7.

9. A coating method, characterized in that: The steps include: The wide temperature range high temperature lubricating coating provided in claim 8 is evenly applied to the surface of the substrate and allowed to dry for 1 to 18 hours to form a pre-coating on the surface of the substrate; Placing the substrate with the pre-coated coating on the surface in a heating device, heating and curing in an air atmosphere to form a coating on the surface of the substrate; During the heating and curing process, the temperature is first raised from room temperature to 120-150°C at a heating rate of 2-3°C / min, and the temperature is kept at this temperature for curing for 1-1.5 hours; then the temperature is raised to 305-315°C at a heating rate of 1-2°C / min, and the temperature is kept at this temperature for curing for 1-1.5 hours, and then the temperature is naturally cooled; The thickness of the cured coating is 15 to 30 μm.

10. A coating, characterized in that: The coating is prepared by the method of claim 9, wherein the thickness of the coating is 15 to 30 μm.

Citation Information

Patent Citations

  • Lubricating protective coating for surface of sliding part in nuclear reactor system

    CN114133769A

  • Lubricating coating based on silane modified aluminum chromium phosphate, preparation method, formed lubricating coating and preparation method of lubricating coating

    CN117143657A

  • Wide-temperature-range self-lubricating coating based on boron nitride / graphene composite filler as well as preparation method and application of wide-temperature-range self-lubricating coating

    CN117363140A

  • Modified boron nitride, preparation method thereof and polyurea coating containing modified boron nitride

    CN118994939A